Feature and classifier development for human detection - Amit Satpathy (2014)
Computer vision has been gaining increasing popularity in this age of automation and advancing technology. The desire to automate a number of labour-intensive tasks and reduce dependence on humans has contributed to this. In particular, human detection has been looked into quite thoroughly in the recent years. Human detection is important in areas of surveillance, pedestrian detection, human-computer interaction etc where humans need to be detected very accurately. With accurate detection, post-processing of human actions can then be done effectively. For accurate detection, it is necessary that the features and classification framework adopted are robust and effective.